Beyond the Obvious Landscapes - Perkins, Elizabeth (LiNQ (Literature in North Queensland), 2016)
Mark O’Connor, The Eating Tree. Sydney: Angus and Robertson, 1980. Paper 5.95. 65pp. Barry O’Donohue, Addiction to False Landscapes. Brisbane: Queensland Community Press, 1981. Paper 5.90. 62 pp. Mark O’Connor’s second volume of collected poems retains the fresh pleasure in nature and the quiet confidence in language that characterize his first collection, Reef Poems. The Eating Tree offers also a thoughtful appraisal of the history of man and nature, and a more conscious delight in the traditional resources of poetry. Formal rhythms, alliteration and consonance, elliptic and contracted phrases, rhyme, double and single epithets, simile and metaphor are used neither lavishly nor sparingly, but occur usually with unarguable justness. Barry O’Donohue was in south-east Asia on National Service, and although his poetry is not overtly autobiographical, moral, political or patriotic, it is the kind of poetry that chronicles where the poet has been in spirit. Names are used as social and moral symbols in the Addiction to False Landscape collection - Kabul, February 1980, Auschwitz, Belsen, Hiroshima, My Lai, Moscow, Peking and Washington - but even in the most realistic of the poems these names have more than political and geographical significance. O’Donohue’s landscape has no fixed reality for himself, and although this does not mean readers cannot look squarely at the landscape of the poems, it does suggest they would be unwise to expect that any kind of fixed reality is normally the subject.